The Influence of Miss Universe Indonesia’s Image on Perceptions of Sexual Harassement Among Generation Z Jabodetabek - Eka Supriyanti Eka; Muhammad Reza; Sabila Adinda Puri Andarini (Jurnal Penelitian Sosial Ilmu Komunikasi, 2024)
Beauty contests have long been part of popular culture, closely related to the image they display, which can influence public perceptions of beauty and gender roles, as well as influencing attitudes towards social issues such as sexual harassment. This study aims to examine how the image displayed by Miss Universe Indonesia influences perceptions of sexual harassment among Generation Z in Jabodetabek. Using a quantitative method that focuses on data in the form of numbers, it was conducted in the Jabodetabek area from January to June 2024. The study population was all Generation Z in Jabodetabek, with samples taken using probability sampling techniques through the simple random sampling method . The results of this study indicate that the value indicator on the image variable obtained an average value of 3.77%, which is included in the high category. Meanwhile, the perpetrator indicator on the perception variable obtained an average value of 3.74%, which is also included in the high category. From the results of the research that has been carried out, it can be concluded that there is an influence between Image and perception, meaning that Ha is accepted while Ho is rejected. Based on the determination test, the image results were 59.9% on perception, while the rest were other variables not explained in this study.